Tracing the Cartography of Nationalism: An Interdisciplinary Perspective Ruskin Bond: Nationalism and Identity (International Journal of Food and Nutritional Sciences, 2022)
Ruskin Bond was born in Kasauli in 1934, and grew up in Jamnagar, Dehradun, Delhi, and Shimla. He is famous for his short stories that range to more than five hundred along with six beautiful novels and three different collections of verses. He also wrote more than 69 books related to children-friendly tales. He received the John Llewellyn Rhys Prize in 1957 for his first novel, The Room on the Roof, the Sahitya Akademi Award in 1992 for Our Trees Still Grow at Dehra, the Padma Shri in 1999 and the Padma Bhushan in 2014. He is a prolific writer and has experimented with several genres of sensibility and emotions. Ruskin Bond introduced several stories and different genres to the world, especially in children's literature.